Tense past, tense present : women writing in English - Kuortti, Joel. (Kolkata : Stree, 2003)
Contributed articles chiefly with reference to some 20th century women authors writing in English from India.
Includes bibliographical references (p. [219]-235).
Keywords: Indic literature (English) -- 20th century -- History and criticism; Indic literature (English) -- Women authors -- History and criticism